Pola Asuh Ibu, Kejadian Diare dan Pertumbuhan Sampai 4 Bulan pada Bayi yang Mengalami Hambatan Pertumbuhan Dalam Rahim - Thresia Dewi Kartini Berek; Zinatul Faizah; Endang Purwaningsih (MEDIA MEDIKA INDONESIANA, 2008)
ABSTRACTMother caring pattern, diarrhea occurrence and growth in the first four months of infants with intra uterine growth retardationBackground: Infants with Intra Uterine Growth Retardation (IUGR) are very sensitive toward infection especially diarrhea. Diarrhea may disrupt growth, while good quality of mother caring pattern improve growth. This study aimed to see the association between mother caring pattern, diarrhea occurrence and the growth of infants with IUGR.Methods: This prospective cohort study was conducted in 44 IUGR infants with from birth to 4 months old. Data were collected by interviews to the mother, using a structured questionnaire and observation. The variables measured were mother caring pattern, diarrhea occurrences, environmental sanitation, health service utility and growth. Data were analyzed using Pearson and Rank-Spearman correlation tests, as well as multiple linear regressions.Results: Eighty-eight point six percents of the respondents had good quality of caring pattern. The mean diarrhea episode per child was 0.84 (±1.1), with duration of 1.8 days/episode. Cummulative incidence of diarrhea was 84.1% and incidence density of diarrhea was 3.1 person-years. Diarrhea occurrences in subjects who were partially breastfed were higher than the subjects who wereexclusively breastfed. There was a correlation between mother’s feeding practice and growth (WAZ: p<0.004, BMI: p<0.039). There was no correlation between mother’s caring pattern, diarrhea occurrences, environmental sanitation, health service utility and growth. Environmental sanitation, health service utility, diarrhea occurrences, mother’s caring pattern of feeding, nursing andhygiene, were all contributed to 31.7% of WAZ scores.Conclusions: Among the mother caring pattern, only feeding practice was correlated to the growth of infants with IUGR, while diarrhea occurrences was not correlated. It is recommended that mothers of infants with IUGR should be given counseling with regard to infant feeding practice.Keywords: Pola Asuh Ibu, Kejadian Diare dan Pertumbuhan Sampai 4 Bulanpada Bayi yang Mengalami Hambatan Pertumbuhan Dalam RahimABSTRAKLatar Belakang: Bayi dengan hambatan pertumbuhan dalam rahim (IUGR) sangat rentan terhadap infeksi terutama diare yang dapat mengganggu pertumbuhannya. Pola asuh ibu diharapkan dapat memperbaiki dan menunjang pertumbuhan optimal bayi yang lahir dengan IUGR. Penelitian ini bertujuan untuk mengetahui hubungan pola asuh ibu dan kejadian diare dengan pertumbuhan bayi dengan IUGR.Metode: Penelitian kohort prospektif pada 44 bayi IUGR sampai umur 4 bulan. Variabel yang diamati: pola asuh ibu, kejadian diare, sanitasi lingkungan, pemanfaatan pelayanan kesehatan dan pertumbuhan. Analisis data dengan korelasi Pearson, Rank- Spearman dan analisis regresi linier ganda.Hasil: Pola asuh ibu 88,6% baik. Rerata episode diare 0,84(±1,16) dengan lama diare 1,8 hari/episode. Insidensi kumulatif diare 84,1% dan densitas insiden diare 3,1 orang-tahun. Kejadian diare subyek ASI parsial lebih banyak dibandingkan subyek ASI eksklusif. Ada hubungan antara praktik ibu memberi makan bayi dengan pertumbuhan bayi (BB/U p<0,004 dan BMI p<0,039). Tidak ada hubungan pola asuh ibu, kejadian diare, sanitasi lingkungan dan pemanfaatan pelayanan kesehatan dengan pertumbuhan bayi. Secara bersama-sama sanitasi lingkungan, pemanfaatan pelayanan kesehatan, kejadian diare, praktik ibu memberi makan,merawat, menjaga kebersihan diri dan bayi berpengaruh terhadap pertumbuhan bayi dengan kontribusi terbesar dari skor-Z BB/U(31,7%).Simpulan: Pada pola asuh ibu hanya praktik ibu memberi makan bayi berhubungan dengan pertumbuhan bayi yang lahir IUGRsampai umur 4 bulan.